prove that if cotx(1+sinx)=4m and cotx(1-sinx)=4n, then (m^2-n^2)^2=mn

Similar Questions
  1. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
  2. The equation 2sinx+sqrt(3)cotx=sinx is partially solved below.2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx)
    1. answers icon 7 answers
  3. 2)Prove the following identities:a)(cosecx + cotx)(cosecx - cotx) = cotxtanx b)2/1+sinx + 1/1-sinx = 3sec^2x - tanxcosecx
    1. answers icon 3 answers
  4. express this in sinx(1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?? and B) express in cosx problem: is 1 +
    1. answers icon 1 answer
more similar questions